Strength and Pain Threshold Handheld Dynamometry Test Reliability in Patellofemoral Pain - van der Heijden, R A; Vollebregt, T; Bierma-Zeinstra, S M A; van Middelkoop, M (International journal of sports medicine, 2015)
Patellofemoral pain syndrome (PFPS), characterized by peri- and retropatellar pain, is a common disorder in young, active people. The etiology is unclear; however, quadriceps strength seems to be a contributing factor, and sensitization might play a role. The study purpose is determining the inter-rater reliability of handheld dynamometry to test both quadriceps strength and pressure pain threshold (PPT), a measure for sensitization, in patients with PFPS. This cross-sectional case-control study comprises 3 quadriceps strength and one PPT measurements performed by 2 independent investigators in 22 PFPS patients and 16 matched controls. Inter-rater reliability was analyzed using intraclass correlation coefficients (ICC) and Bland-Altman plots. Inter-rater reliability of quadriceps strength testing was fair to good in PFPS patients (ICC=0.72) and controls (ICC=0.63). Bland-Altman plots showed an increased difference between assessors when average quadriceps strength values exceeded 250 N. Inter-rater reliability of PPT was excellent in patients (ICC=0.79) and fair to good in controls (ICC=0.52). Handheld dynamometry seems to be a reliable method to test both quadriceps strength and PPT in PFPS patients. Inter-rater reliability was higher in PFPS patients compared to control subjects. With regard to quadriceps testing, a higher variance between assessors occurs when quadriceps strength increases.